Patient and family involvement in decision making for management of cancer patients at a centre in Singapore. Issue 4 (3rd January 2013) - Chong, Jia An; Quah, Yan Ling; Yang, Grace Meijuan; Menon, Sumytra; Radha Krishna, Lalit Kumar
Abstract : Background: The practice of patient autonomy within the prevailing bioethical framework in the West appears increasingly at odds with the prominent influence of the family in medical decision making in the Asian culture. The actual extent of involvement of patient versus the family in the decision making process for cancer management in clinical practice is largely unknown in Asia. Aims: (1) To describe patient and family involvement in healthcare decision making in actual practice, and to determine whether those practices are consistent with Singapore law; and (2) to act as a pilot for a larger prospective study examining the preferences of cancer patients on the decision making process, and the reasons for excluding patients from that process. Methods: A retrospective review of patients who died in an oncology ward in Singapore General Hospital from February to April 2011. Patient and family involvement in discussions on (1) disclosure of diagnosis, (2) initial treatment decisions and (3) initiation of a 'maximum ward management' order was evaluated by reviewing case notes completed by healthcare professionals. Results: Data were collected for 55 patients. Involvement of patients and families at first disclosure of diagnosis was noted in 61% and 64% of cases, respectively. In 12% of cases, the family requested withholding of the diagnosis from the patient. 86% of patients were involved in the initial treatment decisions, and their family was involved in 65% of cases. Only 9% of the 32 alert patients were consulted in end of life decisions. Factors associated with lower patient involvement were advanced age and inability to speak English. Conclusions: While most cancer patients are involved in the healthcare decision making process during the early phase, familial involvement gains prominence as the disease progresses.